PENGARUH EDUKASI 1000 HPK MELALUI MEDIA AUDIO-VISUAL TERHADAP PENGETAHUAN IBU HAMIL - Desi , Desi Laela Fitasari (Jurnal Inovasi Daerah, 2024)
The ongoing nutritional issue and challenge for Indonesia today is stunting. Stunting refers to the condition of malnutrition in toddlers which results in inhibited growth, thereby preventing the child from reaching optimal growth and development, as well as experiencing a decrease in cognitive abilities. Generally, stunting is caused by prolonged insufficient nutrient intake, as well as inadequate caregiving from pregnancy to the first 1000 days after birth. Despite the government implementing policies to reduce the stunting rate, the decrease in stunting rates in Indonesia is still far from the set target. In 2012, the Indonesian government participated in the First 1000 Days of Life Movement aimed at improving the quality of life for Indonesian children in the future by focusing on the first 1000 days of a child's life. This research aims to determine the Influence of HPK 1000 Education Through Audio-Visual Media on the Knowledge of Pregnant Women in Cikakak Village, Wangon II Health Center. This study used pre-experimental research, with a one-group pretest-posttest design evaluation through pretest-posttest. The research sample consisted of 23 pregnant women who were given treatment in the form of 1000 HPK socialization using audio-visual media. The Wilcoxon test results obtained a p-value (0.000) no more than 0.05 indicating that there is a difference in knowledge about 1000 HPK in pregnant women before and after being given educational intervention using audio-visual media. A recommendation that can be given is that in health promotion programs, especially 1000 HPK, there needs to be the use of audio-visual media.